Arbitrage opportunities, liquidity provision, and trader types in an index option market. Issue 3 (21st November 2019) - Chen, Chin‐Ho; Chiu, Junmao; Chung, Huimin
Abstract: This study examines the impact of arbitrage in put–call futures parity (PCFP) violations on option market liquidity and explores the liquidity provision process by trader type during periods of arbitrage exploitation. Using a unique data set comprising the complete history of transactions, we find that PCFP violations contain toxic arbitrage opportunities. Hence, more frequent toxic arbitrage opportunities can cause liquidity to deteriorate because arbitrageurs create adverse selection costs and order imbalances in the option market. In addition, when the law of one price breaks down, market makers dominate by providing liquidity compared with individual, domestic, and foreign institutional traders.